Hubungan Kualitas Pelayanan terhadap Kepuasaan Pelanggan pada Kantor Perusahaan Daerah Air Minum di Kota Sampit Kabupaten Kotawaringin Timur: elationship of Service Quality to Customer Satisfaction in Regional Water Company Office in Sampit City, East Kotawaringin Regency - Handayani, Indah Tri; Marlita, Fitri (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2017)
This study aims to find out and analyze how much the quality of service services relates to the level of satisfaction felt by customers who use the services of Regional Water Companies (PDAMs). The research method used in this study is the observation method, the questionnaire using the Likert scale and the process of determining the sample used is the level of error of 10% as much as 162 samples, the type of research used is associative quantitative that is to find the relationship between service quality and customer satisfaction Testing the hypothesis used is a statistical test with the formula "Product Moment Person". There is a very close relationship between the quality of service to customer satisfaction, from the results of calculations using the product moment person correlation method to get the value of rxy of 0.996 according to the guidelines to provide an interpretation of coefficients the cost is between 0.8-1000. This can be proven that the better or the increased service provided by the PDAM, the higher the level of PDAM customer satisfaction